2486. The Effectiveness of High-Dose Hepatitis B Vaccination in Patients Receiving Immunomodulatory Therapy. (26th November 2018) - Aydin, Murat; Aksoy, Firdevs; Yildirim, Zehra; Koksal, Iftihar
Abstract: Background: The course of hepatitis B virus (HBV) infection is more severe in patients using immunomodulatory drugs (ID) than in the normal population. This study evaluates the results of double-dose administration of HBV vaccine of 40 μg at months 0, 1, 2, and 6. Methods: Anti-HBs negative patients presenting to our polyclinic between January 1 and July 1, 2017 and using ID were administered a double dose of HBV vaccine at months 0, 1, 2, and 6. Patients' primary diseases and comorbid factors were recorded. Anti-HBs titers above 10 mIU/mL 1 month after completion of vaccination schedules were regarded as response to vaccine. Results: Eighty patients presented during the study. Seventeen patients failing to attend follow-ups were excluded. Twenty-eight (44.4%) of the 63 patients enrolled were men and 35(55.6%) were women. Patients' ages ranged between 18 and 66, with a mean age of 44.2 (±12.2) and a median value of 46. Comorbid factors were essential hypertension in 5 patients, diabetes mellitus in 4, and hypothyroid in 3. Vaccination was started within 2 weeks before commencement of ID or simultaneously with a biological agent in 29(46%) patients, and anti-HBs titers above 10 mIU/mL were achieved in 24 (82.8%). Thirty-four (54%) patients were started on vaccination while using medication [mean 21.1(±27.7) months], and anti-HBs titers above 10 mIU/mL were achieved in 29. Response was achieved in 53(84.1%) of all the patients in the study, while no response was obtained in 10 (15.9%). No gender difference was observed between the responding and non-responding patients. Response to vaccine was independent of sex, comorbid diseases, immunosuppressive agents, and time of commencement of vaccination (Table 1). Conclusion: In our study, anti-HBs positivity was achieved in 84.1% of patients receiving doses of 40 μg. Although the ideal situation is for patients to start receiving vaccination at least 2 weeks before starting ID, vaccination in the shortest time possible after commencement of treatment is recommended for previously unvaccinated patients. In conclusion, physicians need not be concerned that response to vaccination cannot be achieved in patients started on ID, and seronegative patients must be enrolled in the HBV vaccination program as quickly as possible. Disclosures: All authors: No reported disclosures.